Exemplarity and the law of superabundance - Savage, Roger W.H. (2016)
Paul Ricoeur’s critique of social emancipatory projects that claim to be absolutely radical sets the stage for my investigation into the exemplary value of esteemed moral and political acts. Like works of art, such acts reform or revolutionize praxis through refashioning the world from within. By placing textual hermeneutics under the theme of the increase in being evinced by the work of art, Ricoeur’s analysis on the way that metaphor as a work in miniature iconically augments reality forges a link between the imagination’s productive power and the “law of superabundance.” This law inheres in the logic of hope. The hope of the “not yet” and the “much more” thus draws support from exemplary acts that bear the mark of the future through testifying to the reign of goodness, generosity, courage and love. However, Ricoeur’s claim that an eschatology of nonviolence constitutes the critique of ideology’s ultimate philosophical horizon raises a question concerning this eschatology’s theological equivalent. Ricoeur maintains that the projection of the task of actualizing freedom is the philosophical equivalent of a theology of hope. This theology draws its meaning from the “hope of things to come” based on the eschatological event. Correlatively, this task’s ethico-political impulse takes root in hope’s practical and existential necessity, which inheres in the structure of action. The hope of as yet unfulfilled expectations and demands ignites the passion for the possible and fuels the will and the desire to intervene in the world’s course. In contrast to the contagion of violence and evil, moral and political acts’ exemplary value stands as a demonstration and proof of hope. The theme of the increase in being that rules over textual hermeneutics consequently has a practical counterpart in the task that an eschatology of nonviolence adopts as its own, namely, the task of actualizing freedom within the historical reality of humankind.
Keywords: Ricoeur, Paul, 1913-2005; Hermeneutics; Eschatology